The impact of vertebral fractures on quality of life in postmenopausal women with osteoporosis. Validity of the Italian version of mini-Osteoporosis Quality of Life Questionnaire - R. Lorenzetti; M. Carotti; A. Stancati; F. Salaffi; W. Grassi (PAGEPress Publications, 2011)
Background: Vertebral fracture is one of the most commonly occurring osteoporotic fractures. Vertebral fractures associated with osteoporosis are a major cause of pain in elderly people and may hardly affect patient's health-related quality of life (HRQOL), making this an important parameter for assessment in these patients. Studies comparing the performance of HRQOL instruments in osteoporosis are laking. Objectives: The purposes of this study were to assess the effect of vertebral fractures on health HRQOL in postmenopausal women with osteoporosis and to investigate the validity of the Italian version of the mini-Osteoporosis Quality of Life Questionnaire (mini-OQOL) in a clinical setting. Methods: Patients were divided into two study groups, according to fracture status: vertebral fractures (41 patients) and no vertebral fractures (27 patients). Baseline assessments of anthropometric data, medical history, and prevalent fracture status were obtained from all participants. All of the participants were evaluated using both disease-targered mini-OQOL and QUALEFFO, generic instrument (EUROQoL), disability scale (Roland Morris Disability questionnaire- RMDQ) and chronic pain grade questionnaire. Results: Vertebral fractures due to osteoporosis significantly decreases scores on physical function, socio-emotional status, clinical symptoms, and overal HRQOL. Both disease-targeted questionnaires showing an association between the number of prevalent vertebral fractures and decreased HRQOL. Significant correlations existed between scores of similar domains of mini-OQOL and the QUALEFFO, especially for symptoms, physical function, activities of daily living and social function. The receiver operating characteristic (ROC) curve analysis of mini-OQOL and the QUALEFFO indicated that both questionnaires were significantly predictive of vertebral fractures. Number of concomitant diseases presented a weak significant correlation with EUROQoL (p=0,041). Conclusions: Our study suggests that the patients with vertebral fractures due to osteoporosis have a relevant impairment in quality of life. Both disease-targeted questionnaires discriminated between patients with and without vertebral fractures though the mini-OQOL, originally developed to measure the effect of vertebral fractures on quality of life, showed slightly better discriminant power. The benefit of the mini-OQOL is that it is efficient, self administered, and requires 3-4 minutes to complete.